A rare case of isolated thoracic AL-amyloidoma causing complete atelectasis of the right lung. (2023) - Rath, Smruti; Dcunha, Nicholas Joseph; Bhan, Neel; Cox, Bettye; Adrish, Muhammad
Abstract: Tumoral amyloidosis, or amyloidoma, is a benign, but rare form of amyloidosis that has been reported with a favorable prognosis following surgical resection in some case reports. We present a case of acute on chronic respiratory failure secondary to extensive growth of a thoracic amyloidoma causing atelectasis of the right lung. Our case patient had greater morbidity due to late presentation and extensive disease at diagnosis, precluding any surgical intervention. Radiation therapy and medical management were unsuccessful in reducing disease burden. Early diagnosis and detection are pivotal to improving survival in patients with isolated thoracic amyloidoma.